Low flush toilet performance assessment of water closets in the transportation of solids - Ilha, Marina Sangoi de Oliveira (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
Water closets represent a high percentage of the domestic water consumption and have a great potential for water savings. This paper presents a laboratory and field investigation that has been conducted by researchers of the State University of Campinas (UNICAMP) and University of São Paulo (USP), with ultra low flush toilets (6.0 litres per flush). The field investigation was developed in 24 low-income houses in Pindamonhangaba, a town in the State of São Paulo. The overall and toilet water consumption was monitored using a telemeter system. A questionnaire was also developed to survey users’ opinion concerning the water closets performance. A comparison between results of the water consumption metering and the questionnaire is shown. A comparative analysis of the results obtained both during field research and laboratory investigation is also made. Finally, proposals for the standardization of low flush toilet performance evaluation are presented.